Mesomorphic phthalocyanine as chemically sensitive coatings for chemical sensors - (:unkn) unknown (ELSEVIER SCIENCE SA, 2003)
Octa(13,17-dioxanonacosane-15-sulfanyl)-substituted mesomorphic nickel(II) phthalocyanine (Pc) at room temperature is investigated for the detection of organic solvent vapors by utilizing quartz crystal microbalance (QCM). Determined by polarized Raman spectroscopy, the Ni(II) Pc layers as coated were disordered and the Ni(II) Pc layers thermally treated were ordered. The ordered films on QCM-devices show higher sensitivity and partition coefficient for all solvent molecules investigated such as ethanol, dichloromethane, acetone, n-hexane. The Raman Spectroscopy investigation results show that the molecules with saturated C-C bonds such as ethanol interact with phthalocyanine films predominantly by formation of hydrogen bonds and the sensor response to pi bond containing compounds such as acetone is the result of their pi-pi interaction with conjugated phthalocyanine ring. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: mesomorphic phthalocyanine; QCM; ordered films; Raman spectra; gas sensitivity; LANGMUIR-BLODGETT-FILMS; RAMAN POLARIZATION; ACOUSTIC-WAVE; ORIENTATION